Determinants of Market Information Infrastructure and Arrivals of Minor Forest Produce (MFP) In High Altitude and Tribal (HAT) Zone of Andhra Pradesh - Kumar, Ch. Satish; Kumar, K. Nirmal Ravi; Paul, K. Solmon Raju; Gopal, P. V. Sathya; Rao, V. Srinivasa (International Journal of Economic Plants, 2023)
Infrastructure facilities on market information are telecommunication systems, computers with internet facilities, adequate working staff and display boards which play significant role in disseminate market information to stakeholders. Market information makes stakeholders to take decision about collection and selling of the forest produce, and it has impact on arrivals of the produce. Present paper deals with the factors influencing infrastructure and arrivals in GCC (Girijan Cooperative Corporation) of HAT zone of Andhra Pradesh. GCC staff and 120 traders were taken for the present study. MLRM (Multiple Linear Regression Model) analysis was employed to study the relationship among both independent and dependent variables. The results of the study indicated that major factors influencing MI infrastructure are quantity of market arrivals of MFP, funds received from GCC significant at 1%, active participation of buyers and sellers significant at 5%. Factors influencing market arrivals are remunerative prices realized for MFP in GPCMS (Girijan Primary Co–operative Marketing Society) /PPCs (Primary Procurement Centers) (relative to prices prevailing in shandies), prompt payment of sales proceeds are significant at 1%, and timely market information from GPCMS/PPCs, availability of good road facility to GPCMS/PPCs significant at 5%. Local government should focus on constructing suitable road facilities, conduct awareness programs about value addition units and educate the tribal farmers about importance of MFP.